CHEAP CHEWSDAY AS A GASTRODIPLOMACY STRATEGY IN INTRODUCING INDONESIAN CULINARY AND CULTURE IN AUSTRALIA - Purwanto, Nanang; Susanto, Gatut; Eka Anggraini, Ade (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
This study explores Cheap Chewsday as a medium of gastrodiplomacy aimed at introducing Indonesian cuisine and culture to the Australian public. Through the participation of Indonesian students in Newcastle, this event serves as a platform to present traditional Indonesian dishes while fostering deep cross-cultural understanding. The findings indicate that Cheap Chewsday successfully attracts local participants interested in exploring the flavors and cultural significance behind Indonesian cuisine. Nevertheless, Indonesian students face challenges in adapting dishes to local preferences, such as modifying spice levels and incorporating accessible ingredients. Positive responses from local participants regarding the uniqueness of Indonesian cuisine suggest that this event effectively facilitates meaningful cultural interactions, enriching cultural awareness between the two communities. Additionally, Cheap Chewsday strengthens the cultural identity of Indonesian students, reinforcing their role as cultural ambassadors in promoting Indonesia abroad. This study concludes that Cheap Chewsday not only introduces Indonesian culinary heritage but also holds potential as a sustainable cultural diplomacy initiative, fostering appreciation of Indonesia’s rich culture among the Australian community.